2023
DOI: 10.3390/bios13050557
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Fingerprint Detection Using Raman and Infrared Spectroscopy Technologies for Cancer Detection: A Progress Review

Abstract: Molecular vibrations play a crucial role in physical chemistry and biochemistry, and Raman and infrared spectroscopy are the two most used techniques for vibrational spectroscopy. These techniques provide unique fingerprints of the molecules in a sample, which can be used to identify the chemical bonds, functional groups, and structures of the molecules. In this review article, recent research and development activities for molecular fingerprint detection using Raman and infrared spectroscopy are discussed, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 153 publications
0
13
0
Order By: Relevance
“…Both ATR-FTIR and SERS techniques are label-free techniques that have been used for the detection of biomolecules in various biological samples. [22][23][24][25] Previous studies have demonstrated the potential of FTIR and SERS techniques for sensitive and accurate detection and analysis of nucleic acids. [26][27][28] For instance, D. Li et al and Y. Li et al utilized SERS to detect miRNA and RNA bases, respectively, achieving improved sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Both ATR-FTIR and SERS techniques are label-free techniques that have been used for the detection of biomolecules in various biological samples. [22][23][24][25] Previous studies have demonstrated the potential of FTIR and SERS techniques for sensitive and accurate detection and analysis of nucleic acids. [26][27][28] For instance, D. Li et al and Y. Li et al utilized SERS to detect miRNA and RNA bases, respectively, achieving improved sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, human blood plasma, a complex biological fluid composed of proteins, lipids, nucleic acids, carbohydrates, etc., is an excellent source for identifying biochemical changes . Therefore, Raman spectroscopy can be used to analyze the spectral signatures of blood plasma and provide valuable diagnostic information. , Raman spectroscopy and other vibrational spectroscopy methods have been used by several groups to investigate their capacity as new diagnostic technologies for a variety of cancers. , …”
Section: Introductionmentioning
confidence: 99%
“…7,8 Raman spectroscopy and other vibrational spectroscopy methods have been used by several groups to investigate their capacity as new diagnostic technologies for a variety of cancers. 9,10 This research mainly focused on the performance of several machine learning models used to discriminate the spectral signatures of human blood plasma samples between lung cancer patients and healthy controls. An ensemble of 16 different machine learning models was examined, including different combinations with a particular feature selection method, transformation techniques, and classifiers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Raman spectroscopy (RS) has been emerging as a potential analytical tool with many ramifications, particularly for rapid, non-invasive and specific disease diagnostics. [14][15][16][17][18][19][20][21] RS is a non-destructive, label-free technique whereby scattered light is used to measure the vibrational modes of a molecule of interest. 22 Originally focused on the characterisation of various analytes in the fields of chemistry and physics, RS has recently been demonstrating unprecedented applications in clinical research ranging from cancer, 18,[23][24][25] infectious diseases 15,26,27 and neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Raman spectroscopy (RS) has been emerging as a potential analytical tool with many ramifications, particularly for rapid, non‐invasive and specific disease diagnostics 14–21 . RS is a non‐destructive, label‐free technique whereby scattered light is used to measure the vibrational modes of a molecule of interest 22 .…”
Section: Introductionmentioning
confidence: 99%